PENGARUH MINAT BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS V SDN 1 KEDUNGWARU TAHUN PELAJARAN 2019/2020 - Imanisa, Shintia; Rizky Ana, Ria Fajrin (Wahana Sekolah Dasar, 2023)
The purpose of this study was to determine the effect of learning interest on student learning outcomes in class V SDN 1 Kedungwaru in the academic year 2019/2020. Methods of data collection using questionnaires and documentation, with ex post facto research and non-experimental design. Sample of 63 students was determined using non-probability sampling techniques. The results of the regression analysis showed the equation Y = 73.594 + 0.100x with tcount> ttable (4.219> 1.999) at a significance level of 5% which showed that the results of Ho were rejected and Ha was accepted. The correlation between learning interest and learning outcomes is 0.475 which shows a moderate relationship with a coefficient of determination of 22.6%. The conclusion of the study, there is the influence of interest in learning towards the learning outcomes of fifth grade students at SDN 1 Kedungwaru in the academic year 2019/2020.Keywords: learning, learning interest, learning outcomes